Sistem Berladang Suku Dayak Kantuk dalam Perspektif Astronomi dan Ilmu Falak - Hesty Kesuma Putri; Ahmad Izzuddin; Mahsun (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2023)
The Dayak Kantuk have a farming custom where the timing of activities is based on the position of celestial bodies. Farming activities are carried out sequentially including looking for land, slashing, cutting, burning, planting rice seeds, clearing grass, harvesting and Gawai Dayak. This research is included in ethnoastronomy research. Data collection was carried out by means of a literature study. Then the data were analyzed using content analysis and observation techniques. The results showed that the Dayak Kantuk used the luni-solar calendar system to determine farming time. The position of the stars is used as a tool to determine the season. The connection with astronomy is that the determination of the month is equally based on the moon in the sky. However, because the Dayak Kantuk also apply the seasons as the basis for the calendar, the month counts cannot go hand in hand. On the other hand, global rashdul qibla occurs exactly a week after the Gawai Dayak event, so that the Dayak Kantuk Muslim community can measure the Qibla direction exactly a week after the Gawai event.